The master handbook of IC circuits - Horn, Delton T. (New York : McGraw Hill Education, 1997)
Put an easy-to-use arsenal of IC applications data right at your fingertips! Complete with new features that make it even easier to use than its predecessors, this third edition of a best-selling handbook provides extensive data on application circuits for today's most popular integrated circuits. It's an ideal companion volume to The Master IC Cookbook, Third Edition, and covers hundreds of currently available ICs. Similar applications for the same type of IC are guouped together for easy comparison, and the larger format of this edition makes the illustrations and text more readable. New circuits have been added, while obsolete and unavailable devices have been deleted to keep you up to date. Only ICs commercially available from major hobbyist suppliers at the time of publication have been included. Special attention is given to sub-families of the 74xx series, and a new section on analog/digital and digital/analog converters encompasses increasingly common hybrid devices that blend digital and linear circuitry. Sections organized conveniently by type of IC include coverage of: 4xxx digital circuits; operational amplifiers and comparators; oscillators and signal generators; audio amplifers; voltage regulators; RF and video devices; special-purpose digital and computer-related circuits. Combining comprehensiveness with easy access and readability, The Master Handbook of IC Circuit Applications, Third Edition will greatly expedite your IC expertise.
Section 1 74xx digital -- Section 2. 4xxx digital -- Section 3. Special-purpose digital -- Section 4. Operational amplifiers and comparators -- Section 5. Audio amplifiers -- Section 6. Timers, oscillators, and signal generators -- Section 7. RF amplifiers and related devices -- Section 8. Voltage regulators and power supply devices -- Section 9. Other linear devices -- Section 10. Digital/analog hybrids.
Includes index.
Keywords: INTEGRATED CIRCUITS